Review of the physical and physiological demands of surfing and suggested training modalities and exercises - Secomb, J. L. (Journal of Australian Strength and Conditioning, 2012)
Surfing has recently experienced a significant increase in public and commercial interests, which has resulted in a more professional approach being taken to the sport. Whilst a comprehensive profile of the physical and physiological requirements of surfing is yet to be achieved, significant findings have been reported on; movement characteristics of surfing specific activities, the heart rate (HR), blood lactate concentration ([BLa-]), oxygen consumption (VO2), and peak power output (PPO) responses during laboratory and ocean based tests, as well as time-motion characteristics of surfing activity. It is evident from this review that the physical and physiological requirements of surfboard paddling include; upper body muscular endurance, strength, and power, intermittent endurance, aerobic and anaerobic power, and lactate tolerance and clearance. Conversely, wave riding requires; lower body muscular strength, dynamic balance, single leg strength, and rotational power. It is apparent that surfers require an integration of several highly-developed physiological systems to be successful, and hence, it is imperative for the strength and conditioning (S&C) coach to prescribe training modalities and exercises aimed at developing these capacities to the greatest functional level. Whilst the findings reported on the physical and physiological requirements of surfing thus far can assist the S&C coach with effective training prescription for a surfer, further research is required to develop a more thorough understanding of these requirements.